Financial Self Efficacy Memediasi Mental Accounting dan Literasi Keuangan Terhadap Perilaku Pengelolaan Keuangan - Manzala, Aura; Susilowati, Endah (Jurnal Riset Pendidikan Ekonomi, 2025)
Many individuals still face difficulties in managing their finances due to a limited understanding of personal financial management. University students, as part of the younger generation dealing with academic pressures and future uncertainty, are particularly vulnerable to financial management problems. This research aims to determine the effect of financial self-efficacy in mediating mental accounting and financial literacy on financial management behavior. This study uses primary data sources with quantitative research types. Sampling used a random sampling technique. The sample used was active Accounting students from three public universities in Surabaya, with analysis carried out using SmartPLS4 software. Based on the test results, it can be concluded that mental accounting, financial literacy, and financial self-efficacy play an important role in influencing the formation of individual financial management behavior. Mental accounting and financial literacy directly influence financial management behavior. In addition, financial self-efficacy mediates between financial literacy and financial management behavior, but not the relationship between mental accounting and financial management behavior. The implications of this study highlight the importance of improving financial literacy and applying mental accounting to strengthen healthy financial management behavior among university students.